A comprehensive review on the proton conductivity of proton exchange membranes (PEMs) under anhydrous conditions: Proton conductivity upper bound. (6th October 2021) - Karimi, Mohammad Bagher; Hooshyari, Khadijeh; Salarizadeh, Parisa; Beydaghi, Hossein; Ortiz- Martínez, V.M.; Ortiz, A.; Ortiz Uribe, I.; Mohammadi, Fereidoon
Abstract: The present study aims to assess the proton conductivities of the most investigated proton exchange membranes (PEMs) used in PEM fuel cells (PEMFCs). Specifically, PEMs are analyzed for their use in anhydrous fuel cells and proton conductivity upper bounds were provided for them. Considering the direct relationship between proton conductivity and temperature, an upper bound is presented. Based on the obtained upper bounds, suitable membranes for high-temperature performance are determined, and the average range of proton conductivity for each polymer group is discussed. By comparing the available proton conductivity data with upper bound, it was demonstrated that some of poly (ionic liquid)s have provided the highest proton conductivities, however aromatic polymers such as polybenzimidazole (PBI) are found more suitable choices for application at anhydrous conditions and high temperatures. The proton conductivity upper bound for anhydrous PEMs demonstrates the availability of promising polymer options for the deployment of anhydrous fuel cells. Highlights: The proton conductivity of the most investigated PEMs used in anhydrous fuel cells was investigated. The proton conductivity upper bound for anhydrous PEMs was presented. Nafion, polybenzimidazole and polyetheretherketone are the most investigated polymers for anhydrous fuel cells.